A heparin-like interpenetrating network CRRT hollow fiber dialysis membrane, a preparation method and application thereof
Patent Information
- Application Number
- CN202611116810.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-23
AI Technical Summary
本发明通过将合适磺化度的短侧链型磺化聚芳醚砜(SPAES)与磺化聚乙烯醇(SPVA)进行复合纺丝,利用SPAES提供力学骨架和结构稳定性、SPVA提供类肝素生物活性和超亲水表面,实现“刚柔并济”的协同增效,同时解决现有CRRT透析膜抗凝性能不足、中分子清除效率低和力学性能不佳的技术问题
[0034](1)优异的抗凝血性能(类肝素效应)
Smart Images

Figure CN122955374A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of blood purification membrane materials technology, specifically to a heparin-like interpenetrating network continuous renal replacement therapy (CRRT) hollow fiber dialysis membrane and its preparation method, particularly to a heparin-like active hollow fiber dialysis membrane prepared by composite spinning of short-side-chain sulfonated polyarylene ether sulfone (SPAES) and sulfonated polyvinyl alcohol (SPVA). This invention also relates to the application of the hollow fiber dialysis membrane in the preparation of filters for blood purification therapy in patients with sepsis-related acute kidney injury and multiple organ dysfunction syndrome. Background Technology
[0002] Continuous Renal Replacement Therapy (CRRT) is a blood purification therapy used for critically ill patients with acute renal failure, sepsis, etc. It is usually performed as a single treatment lasting 24 to 48 hours at a blood flow rate of 50 to 150 mL / min. CRRT places much higher demands on the performance of the dialysis membrane than conventional hemodialysis, mainly in the following aspects: (1) long-term operational stability; (2) highly efficient clearance of medium-molecular-weight toxins and inflammatory cytokines; and (3) excellent blood compatibility and anticoagulant properties.
[0003] Currently, the CRRT dialysis membranes commonly used in clinical practice mainly have the following technical defects:
[0004] (1) Insufficient anticoagulant properties, relying on exogenous heparin. Existing dialysis membrane materials such as polyethersulfone (PES) and polysulfone (PSF) are highly hydrophobic, easily causing protein adsorption and platelet adhesion when in contact with blood, leading to thrombosis. In clinical practice, continuous infusion of anticoagulants such as heparin is required, increasing the risk of bleeding in patients, especially during CRRT treatment which lasts 24-48 hours. Although some studies have attempted to modify polysulfone by sulfonation before heparin grafting, the heparin grafting process is complex, costly, and carries the risk of heparin shedding.
[0005] (2) Low clearance efficiency of medium-molecular-weight toxins and cytokines. One of the core treatment goals of CRRT is to remove excessive inflammatory cytokines (such as IL-6, IL-8, etc., with a molecular weight of 15~26 kDa) from the blood to block the "cytokine storm". Although existing products such as oXiris membranes have a certain cytokine adsorption capacity, their core material is acrylonitrile-sodium methyl propylene sulfonate copolymer, which has limited mechanical properties and chemical stability (Baxter Healthcare Corporation. oXiris®Membrane Product Technical Manual. 2018).
[0006] (3) The contradiction between "permeability and selectivity" is prominent. Traditional dialysis membranes cannot simultaneously achieve high-flux water permeability and high-selectivity retention. Although increasing the membrane pore size can enhance the removal of medium-molecular-weight toxins, it often leads to a large loss of beneficial proteins such as albumin.
[0007] (4) Existing modification schemes are difficult to achieve a synergistic unity between rigid framework and flexible function, and there are common technical bottlenecks. To overcome the above defects, researchers have tried a variety of modification strategies, but none of them have been able to balance mechanical properties, anticoagulant activity and long-term stability: On the one hand, single material systems have inherent performance shortcomings. Although short-side-chain sulfonated polyarylene ether sulfone (SPAES) has excellent thermal stability, mechanical properties and biocompatibility, when used alone, the density and distribution of sulfonic acid groups on its surface are difficult to reach the ideal level of heparin-like bioactivity. Excessive sulfonation will lead to excessive swelling of the membrane and deterioration of mechanical properties. Sulfonated polyvinyl alcohol (SPVA) has heparin-like bioactivity due to the presence of sulfonic acid groups, which can significantly prolong clotting time and inhibit platelet adhesion, but its mechanical strength is insufficient when it forms a film alone. It is prone to excessive swelling or even dissolution in an aqueous environment, and cannot meet the mechanical requirements of long-term operation of CRRT. On the other hand, existing composite modification strategies (blending method and coating method) have structural defects. While blending modification strategies (such as Chinese patent application CN117643807A, which disperses sulfonated polyarylene ether copolymers in a polyethersulfone matrix) can improve hydrophilicity and charge effects, the sulfonated polymer exists only as a dispersed phase and fails to form a continuous mechanical framework and functional network. Furthermore, it does not introduce a flexible polymer component with heparin-like bioactivity, and its anticoagulant properties still rely on the passive charge effect on the material surface, lacking an active anticoagulant biological mechanism. Although international patent application WO2020 / 130823A1 involves blending sulfonated poly(arylene ether sulfone) with non-sulfonated polymers, it does not involve polyvinyl alcohol or sulfonated polyvinyl alcohol components, nor does it mention a technical solution for constructing an interpenetrating network structure through chemical crosslinking. While surface coating modification strategies (such as Chinese patent application CN119857370A, which coats an anticoagulant functional layer on the basement membrane surface using a dopamine-assisted method) can improve anticoagulant performance, the lack of chemical bonding between the functional layer and the substrate leads to a significant risk of coating detachment during long-term use. Furthermore, surface modification cannot alter the sieving performance and mechanical properties of the membrane itself (Journal of Membrane Science, 2016, 512: 45–52).
[0008] In summary, while existing technologies have recognized the importance of sulfonation modification, neither blending nor surface coating modifications have solved the dual technical challenges of stable chemical bonding and synergistic network construction between the "rigid mechanical framework" and the "flexible heparin-like functional layer." Specifically, there is currently no technical inspiration for constructing an interpenetrating network structure by chemically crosslinking the rigid backbone of short-side-chain sulfonated polyarylene ether sulfone with the heparin-like flexible segments of sulfonated polyvinyl alcohol, and using it for bulk modification of CRRT hollow fiber dialysis membranes. Therefore, there is an urgent need to develop a CRRT dialysis membrane that combines excellent mechanical properties, heparin-like anticoagulant activity, efficient medium-molecular-weight scavenging ability, and long-term antifouling stability. Summary of the Invention
[0009] This invention addresses the aforementioned technical problems in existing technologies by providing a heparin-like interpenetrating network (IPN) hollow fiber dialysis membrane for CRRT, its preparation method, and its applications. This invention achieves a synergistic effect of "rigidity and flexibility" by composite spinning of short-side-chain sulfonated polyarylene ether sulfone (SPAES) with appropriate sulfonation degree and sulfonated polyvinyl alcohol (SPVA). SPAES provides the mechanical framework and structural stability, while SPVA provides heparin-like bioactivity and a superhydrophilic surface. This simultaneously solves the technical problems of insufficient anticoagulation performance, low medium-molecule clearance efficiency, and poor mechanical properties in existing CRRT dialysis membranes. The specific technical solution is as follows:
[0010] A heparin-like interpenetrating network (IPN) hollow fiber dialysis membrane for CRRT comprises short-side-chain sulfonated polyarylene ether sulfone and sulfonated polyvinyl alcohol. The short-side-chain sulfonated polyarylene ether sulfone and sulfonated polyvinyl alcohol form an interpenetrating network structure through chemical crosslinking or physical crosslinking. The chemical crosslinking is achieved by forming covalent crosslinking points through esterification reactions between sulfonic acid groups on the short-side-chain sulfonated polyarylene ether sulfone segments and hydroxyl groups on the sulfonated polyvinyl alcohol segments. The physical crosslinking is achieved through at least one of the following: hydrogen bonding between sulfonic acid groups on the short-side-chain sulfonated polyarylene ether sulfone segments and hydroxyl groups on the sulfonated polyvinyl alcohol segments; ionic crosslinking between sulfonic acid groups and multivalent metal ions; or hydrophobic interactions between polymer segments.
[0011] Furthermore, the sulfonic acid groups of the short-side-chain sulfonated polyarylene sulfone are connected to the polyarylene sulfone main chain by a linking chain of no more than 3 atoms, and the side chain length is less than or equal to 6 atoms.
[0012] Furthermore, the connecting chain is –C3H6– or –C6H4–.
[0013] Furthermore, the degree of sulfonation of the short-side-chain sulfonated polyarylene sulfone is 30%~70%, preferably 40%~60%; the degree of sulfonation of the sulfonated polyvinyl alcohol is 20%~60%, preferably 30%~50%.
[0014] Furthermore, the mass ratio of the short-side-chain sulfonated polyarylether sulfone to sulfonated polyvinyl alcohol is 9:1 to 5:5, preferably 7:3 to 6:4.
[0015] Furthermore, the hollow fiber membrane has an asymmetrical structure, with a dense separation layer on the inner surface and a sponge-like support structure on the outer surface and inside the membrane wall.
[0016] A method for preparing the heparin-like interpenetrating network CRRT hollow fiber dialysis membrane includes the following steps:
[0017] (1) Dissolve short-side-chain sulfonated polyarylether sulfone and sulfonated polyvinyl alcohol in a common solvent at a mass ratio of 9:1 to 5:5, and stir at 60 to 100°C for 4 to 12 hours to form a homogeneous casting solution.
[0018] (2) Add crosslinking agent and pore-forming additive to the casting solution, continue stirring for 2-4 hours, and let stand to degas for 12-24 hours; the crosslinking agent is selected from at least one of glutaraldehyde, epoxy resin or thermal crosslinking agent; the pore-forming additive is selected from at least one of polyvinylpyrrolidone and polyethylene glycol;
[0019] (3) The degassed casting liquid is extruded through the hollow fiber spinning spinneret and solidified in the coagulation bath through a dry-wet spinning process to form the hollow fiber membrane filament.
[0020] (4) After the hollow fiber membrane nascent fibers are completely solidified in a coagulation bath, they are washed with water, subjected to heat treatment for crosslinking, plasticized with glycerol, and dried to obtain the hollow fiber dialysis membrane.
[0021] Furthermore, the common solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, and N,N-dimethylformamide.
[0022] Furthermore, the process parameters of the dry-wet spinning process in step (3) are: extrusion speed 5~30 m / min, dry spinning length 5~50 cm, coagulation bath temperature 20~60℃; the temperature of the heat treatment crosslinking in step (4) is 80~150℃, and the time is 2~8 hours.
[0023] The application of the heparin-like interpenetrating network (CRRT) hollow fiber dialysis membrane in the preparation of blood purification filters for continuous renal replacement therapy.
[0024] Technical principles and mechanisms of action of the present invention
[0025] (1) Interpenetrating network structure with "combination of rigidity and flexibility"
[0026] The short-chain sulfonated polyarylene ether sulfone (SPAES) has a rigid aromatic backbone, endowing the membrane material with excellent mechanical properties and thermal stability. Sulfonated polyvinyl alcohol (SPVA) has a flexible molecular chain, providing the membrane material with excellent hydrophilicity and heparin-like bioactivity. The two form an interpenetrating network structure through chemical cross-linking. The rigid segments of SPAES act as the "backbone," resisting excessive swelling and deformation of the membrane, while the flexible segments of SPVA act as "functional units," providing anticoagulant and antifouling activities, achieving a synergistic balance between mechanical properties and bioactivity. In addition to chemical cross-linking, the sulfonic acid groups on the SPAES backbone and the hydroxyl groups on the SPVA segments can also form physical cross-linking points through hydrogen bonding, further enhancing the stability of the interpenetrating network. Furthermore, when the degree of sulfonation of SPVA is high, the sulfonic acid groups can form physical cross-links through ionic cross-linking (such as coordination with multivalent metal ions) or hydrophobic interactions. Chemical cross-linking provides permanent covalent bonds, while physical cross-linking endows the network structure with a certain degree of reversibility and self-healing ability. The synergy of both can further improve the long-term operational stability of the membrane.
[0027] (2) Heparin-like anticoagulation mechanism
[0028] The sulfonic acid group (–SO3H) introduced into the SPVA molecular chain can mimic the structure and function of heparin. Through electrostatic interactions, the sulfonic acid group binds to antithrombin III (AT-III), inducing a conformational change in AT-III, significantly enhancing its inhibitory activity against coagulation factors (especially thrombin and factor Xa), thereby prolonging clotting time and inhibiting thrombus formation. Simultaneously, the strong negative charge of the sulfonic acid group repels similarly negatively charged platelets and plasma proteins, reducing platelet adhesion and protein adsorption.
[0029] (3) Hydrophilic and anti-fouling surface
[0030] SPVA's superhydrophilicity enables the formation of a robust hydration layer on the membrane surface, effectively resisting irreversible protein adsorption and deposition. Combined with the rigid framework support of SPAES, the composite membrane can maintain high flux during long-term operation, significantly extending the membrane's lifespan.
[0031] (4) Precisely controlled dual function of sieving and adsorption
[0032] By adjusting the sulfonation degree of SPAES side chains (30%~70%) and SPVA (20%~60%), as well as their blending ratio, synergistic control of membrane pore size and membrane surface charge density can be achieved. Membrane pore size determines the solute sieving and retention performance, while surface charge density determines the electrostatic adsorption capacity for positively charged cytokines, thereby realizing a dual purification mechanism of "dialysis removal" and "adsorption removal".
[0033] Beneficial effects
[0034] (1) Excellent anticoagulant properties (heparin-like effect)
[0035] The sulfonic acid groups of SPVA endow the composite membrane with heparin-like bioactivity, and the anticoagulant effect is positively correlated with the SPVA content and degree of sulfonation. The plasma recalcification time (PRT) of the composite hollow fiber dialysis membrane of this invention is extended from 220 s of the pure SPAES membrane to 363 s, an extension of 65%; the number of platelets adhering is reduced by more than 60%. As shown in Example 3, when the mass ratio of SPAES / SPVA is 6:4, the PRT extension can reach 70%. This invention can achieve heparin-free or low-heparinization dialysis, significantly reducing the bleeding risk in CRRT treatment. In contrast, although the existing oXiris membrane (AN69ST substrate) has cytokine adsorption capacity, its anticoagulant performance still depends on systemic heparinization administration and cannot achieve heparin-like anticoagulation of the material itself.
[0036] (2) Highly efficient clearance of medium-molecular-weight toxins and cytokines
[0037] This invention achieves highly efficient removal of medium-molecular-weight toxins and inflammatory cytokines through precise control of membrane pore size (molecular weight cutoff 30-60 kDa) and synergistic adsorption of negative charges on the membrane surface.
[0038] (3) The unity of high throughput and high selectivity
[0039] This invention achieves high selective retention of albumin while maintaining high permeability. This synergistic effect of "high flux-high retention" resolves the contradiction between "permeability-selectivity" in traditional dialysis membranes and is also superior to the conventional performance level of oXiris membranes (membrane area 1.5 m2, maximum transmembrane pressure ≥ 450 mmHg / 60 kPa).
[0040] (4) Excellent anti-pollution performance and long-term operational stability
[0041] SPVA's superhydrophilic surface gives the composite membrane excellent resistance to protein fouling. After three-cycle BSA filtration testing, the flux recovery rate (FRR) is ≥90%. Thanks to the rigid framework support and chemical cross-linking network of SPVA, the composite membrane exhibits a flux decay rate ≤18% and a mechanical property retention rate ≥85% after 48 hours of continuous operation under simulated CRRT conditions.
[0042] Clinical Application Value: Based on a 48-hour CRRT treatment period, the flux attenuation rate of this invention is ≤18%, meaning that filter replacement is unnecessary during treatment. In contrast, the median replacement time for existing CRRT filters due to coagulation blockage is only 35 hours (interquartile range 20-44 hours), requiring at least one filter replacement for many patients within a 48-hour treatment cycle. Coagulation blockage caused by filter replacement accounts for 15.4%-22.9% of all filter replacement causes. Based on an annual CRRT treatment volume of 1000 cases, using the membrane material of this invention can reduce filter replacements by approximately 300-500 cases per year, significantly reducing patient trauma, infection risk, and medical costs.
[0043] (5) Excellent mechanical properties
[0044] The tensile strength of this invention is ≥25 MPa and the elongation at break is ≥10%, which meets the mechanical requirements of CRRT filters for hollow fiber membranes and is also superior to the conventional mechanical properties of oXiris membranes (AN69-based acrylonitrile-sodium methanesulfonate copolymer).
[0045] (6) The preparation process is simple and suitable for industrialization.
[0046] This invention employs a conventional dry-wet spinning process to prepare hollow fiber membranes. The process flow is fully compatible with existing polyethersulfone hollow fiber membrane production lines, requiring no large-scale equipment modifications. All raw materials are bulk chemicals; SPES can be mass-produced using a mature electrophilic sulfonation method, and SPVA can be mass-produced using an SO3·pyridine complex method. The total production cost can be controlled within 120% of the cost of existing PES hollow fiber membranes, demonstrating promising industrialization prospects. Attached Figure Description
[0047] Figure 1 This is a scanning electron microscope (SEM) image of the full cross-sectional structure of the composite hollow fiber dialysis membrane of the present invention.
[0048] Figure 2 This is a magnified scanning electron microscope (SEM) image of the inner surface separation layer of the cross-section of the composite hollow fiber dialysis membrane of the present invention.
[0049] Figure 3 This is a magnified scanning electron microscope (SEM) image of the outer surface and sponge-like structure of the membrane wall of the composite hollow fiber dialysis membrane of the present invention. Detailed Implementation
[0050] The invention will now be further described with reference to the accompanying drawings.
[0051] The heparin-like interpenetrating network CRRT hollow fiber dialysis membrane of the present invention comprises short-side-chain sulfonated polyarylene ether sulfone (SPAES) and sulfonated polyvinyl alcohol (SPVA), wherein the SPAES and SPVA form an interpenetrating network structure through chemical crosslinking and / or physical crosslinking; the chemical crosslinking is selected from covalent crosslinking, and the physical crosslinking is selected from at least one of hydrogen bonding crosslinking, ionic crosslinking or hydrophobic interaction.
[0052] Short side chain type refers to the sulfonic acid group being connected to the polyarylether sulfone main chain by a linking chain of no more than 3 atoms, with a side chain length of less than or equal to 6 atoms; the linking chain is preferably –C3H6– or –C6H4–.
[0053] The general structural formula of short-side-chain sulfonated polyarylene ether sulfone is shown in formula (I):
[0054]
[0055] Formula (I)
[0056] The degree of sulfonation of short-side-chain sulfonated polyarylene sulfone is 30% to 70%, more preferably 40% to 60%.
[0057] Sulfonated polyvinyl alcohol is shown in formula (II):
[0058]
[0059] Equation (II)
[0060] The degree of sulfonation of sulfonated polyvinyl alcohol is 20% to 60%, more preferably 30% to 50%.
[0061] The plasma recalcification time (PRT) of the hollow fiber dialysis membrane is more than 1.5 times that of the pure SPAES membrane, and the number of platelets adhering is reduced by more than 50%.
[0062] The mass ratio of short-side-chain sulfonated polyarylene sulfone to sulfonated polyvinyl alcohol is 9:1 to 5:5, more preferably 8:2 to 6:4.
[0063] Chemical crosslinking is at least one of thermal crosslinking, glutaraldehyde crosslinking, or esterification crosslinking.
[0064] Hollow fiber membranes have an asymmetric structure, with a dense separation layer on the inner surface and a sponge-like support structure on the outer surface and inside the membrane wall.
[0065] The method for preparing the heparin-like interpenetrating network CRRT hollow fiber dialysis membrane of the present invention includes the following steps:
[0066] Step 1: Polymer Synthesis
[0067] (1) Synthesis of short-side-chain sulfonated polyarylene ether sulfones (SPAES):
[0068] Synthesis of Intermediate Product 1: 4,4'-difluorodiphenyl sulfone (15.2 g, 0.06 mol), 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone (13.0 g, 0.05 mol), and potassium carbonate (20.7 g, 0.15 mol) were added to a 250 mL three-necked flask equipped with nitrogen protection, a Dean-Stark water separator, and a condenser; 200 mL of DMAc and 60 mL of toluene were added, and the mixture was reacted at 140 °C with stirring for 4 h. After removing the toluene, the temperature was raised to 165 °C and reacted for 7 h. After cooling, the reaction solution was slowly poured into methanol / water (1:1, v / v) to precipitate the product. After filtration, the product was washed three times with methanol and deionized water, respectively, and dried under vacuum at 60 °C for 24 h to obtain a polyarylene ether sulfone intermediate containing amino and hydroxyl bifunctional groups, with the structural formula shown in Formula (III) (Intermediate Product 1, yield approximately 92%).
[0069]
[0070] Synthesis of Intermediate Product 2: 5.0 g of Intermediate Product 1 was added to a 100 mL three-necked flask equipped with nitrogen and a condenser. 100 mL of DMAc was added to completely dissolve the product, followed by the addition of 1.3 g (1.1 equiv., relative to the molar number of amino groups) of 1,3-propanesulfonic acid lactone. The reaction was carried out at 70°C for 15 h. After the solution cooled to room temperature, it was poured into isopropanol to precipitate the product. The precipitate was repeatedly washed with deionized water until neutral and dried under vacuum at 60 °C for 24 h to obtain Intermediate Product 2 (yield approximately 88%). In this step, 1,3-propanesulfonic acid lactone, as a highly reactive cyclic sulfonate, undergoes a nucleophilic ring-opening reaction with the primary amino group (–NH2) on the polymer side chain to generate a secondary amine sulfonic acid structure containing a sulfonic acid group (–SO3H), as shown in Formula (Ⅳ). This reaction does not require a catalyst and can be carried out under mild conditions.
[0071]
[0072] Equation (Ⅳ)
[0073] Synthesis of Intermediate Product III: Hydroquinone (4.4 g, 0.04 mol), sodium hydroxide (2.0 g, 0.05 mol), and 1,6-dibromohexane (4.9 g, 0.02 mol) were dissolved in 100 mL of ethanol and refluxed at 80 °C for 6 h under nitrogen protection. During the reaction, hydroquinone formed sodium phenolate under alkaline conditions, which underwent a nucleophilic substitution reaction with 1,6-dibromohexane to generate 1,6-di(4-hydroxyphenoxy)hexane. The reaction solution was poured into deionized water, and the pH was adjusted to 7 with 0.1 M sulfuric acid. The precipitated white precipitate was filtered, washed repeatedly with deionized water, and dried under vacuum at 60 °C for 24 h to obtain the structural formula of Intermediate Product III, as shown in Formula (V) (yield approximately 85%).
[0074]
[0075] Formula (V)
[0076] Synthesis of SPAES: Product 2 (5.0 g), Product 3 (1.0 g), and potassium carbonate (0.5 g) were added to a 100 mL three-necked flask equipped with nitrogen and a condenser. 30 mL of DMAc was added and stirred to dissolve the product. The reaction mixture was reacted at 160 °C for 2 h. The reaction solution was slowly poured into deionized water to precipitate the product. After washing repeatedly with deionized water, the product was dried under vacuum at 60 °C for 24 h to obtain short-chain sulfonated polyarylene ether sulfones (SPAES). In this step, the phenolic hydroxyl groups on Product 3 formed phenoxy anions under the action of potassium carbonate, which underwent nucleophilic substitution of the aryl fluorine groups at the end of Product 2, thus extending the polymer chain. The molecular weight of the final polymer was controlled by adjusting the feed ratio of Product 2 to Product 3. The degree of sulfonation of the obtained SPAES was determined by 1H-NMR to be X% (based on the average number of sulfonic acid groups per repeating unit).
[0077] (2) Synthesis of sulfonated polyvinyl alcohol (SPVA):
[0078] Weigh 10.0 g of polyvinyl alcohol (PVA, degree of hydrolysis ≥98%, Mw ≈ 85,000–124,000) and add it to 100 mL of dimethyl sulfoxide (DMSO). Stir at 90 °C for 4 h until completely dissolved to obtain a homogeneous and transparent solution. Then, cool the system to an ice-water bath at 0–5 °C. Dissolve 1.5 mL of chlorosulfonic acid (ClSO3H) in 10 mL of DMSO and slowly add it dropwise to the PVA solution over a period of at least 30 min to avoid excessive local sulfonation and side reactions. After the addition is complete, continue stirring in an ice bath for 30 min, then raise the temperature to 5 °C and react for 6 h.
[0079] After the reaction was complete, the reaction solution was slowly poured into 500 mL of anhydrous ethanol for precipitation. The precipitated polymer was collected by filtration and washed repeatedly with anhydrous ethanol 3–5 times until the washing solution was neutral. The obtained product was dried in a vacuum drying oven at 60 °C for 24 h to obtain sulfonated polyvinyl alcohol (SPVA) powder. ¹H-NMR analysis showed that the degree of sulfonation of SPVA under these conditions was approximately 40%. The degree of sulfonation could be controlled within the range of 20%–60% by adjusting the amount of chlorosulfonic acid added (1.0–3.0 mL) and the reaction time (4–12 h).
[0080] The IEC value of SPVA-40 was determined by 1H-NMR (using D2O as solvent, with the –CH2–CH(OH)– main chain proton peak at δ 3.6–4.0 ppm as an internal standard) and verified by acid-base titration. The IEC value was approximately 1.6 mmol / g. By adjusting the amount of chlorosulfonic acid added (1.0–3.0 mL) and the reaction time (4–12 h), the IEC of SPVA could be controlled within the range of 0.8–2.4 mmol / g, corresponding to a sulfonation degree of 20%–60%.
[0081] Step 2: Preparation of Casting Solution
[0082] Short-chain sulfonated polyarylene ether sulfone (SPAES) and sulfonated polyvinyl alcohol (SPVA) are dissolved in a common solvent at a mass ratio of 9:1 to 5:5, and stirred at 60 to 100°C for 4 to 12 hours to form a homogeneous casting solution; the common solvent is selected from at least one of N-methylpyrrolidone (NMP), N,N'-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), and N,N'-dimethylformamide (DMF).
[0083] The degree of sulfonation of the short-chain sulfonated polyarylene ether sulfone is 30%~70%, more preferably 40%~60%. When the degree of sulfonation is below 30%, the hydrophilicity of SPVA is insufficient, and the membrane surface's resistance to protein adsorption decreases significantly. When it is above 70%, excessive swelling of the membrane leads to deterioration of dimensional stability and mechanical properties. The degree of sulfonation of the sulfonated polyvinyl alcohol is 20%~60%, more preferably 30%~50%. When the degree of sulfonation is below 20%, the heparin-like activity of SPVA is insufficient, and the improvement in anticoagulant performance is not significant. When it is above 60%, the water solubility of SPVA is too strong, and the composite membrane has the risk of slow dissolution during long-term operation in an aqueous environment. The mass ratio of the short-chain sulfonated polyarylene ether sulfone to sulfonated polyvinyl alcohol is 9:1~5:5, more preferably 8:2~6:4. When the mass ratio is above 9:1, the SPVA content is too low, and the improvement in anticoagulant performance is not significant. When it is below 5:5, the SPVA content is insufficient, and the mechanical properties and dimensional stability of the composite membrane deteriorate.
[0084] Step 3: Addition of crosslinking agent and pore-forming additive
[0085] Add a crosslinking agent and a pore-forming additive to the casting solution, continue stirring for 2-4 hours, and let stand for 12-24 hours to remove bubbles; the crosslinking agent is selected from at least one of glutaraldehyde, epoxy resin or thermal crosslinking agent; the pore-forming additive is selected from at least one of polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG).
[0086] Step 4: Dry-wet spinning of hollow fiber membranes
[0087] The degassed casting solution is extruded through a hollow fiber spinning spinneret and then solidified in a coagulation bath via a dry-wet spinning process to form a hollow fiber membrane nascent filament. The process parameters of the dry-wet spinning process are: extrusion speed of 5~30 m / min, dry spinning length of 5~50 cm, coagulation bath temperature of 20~60℃, and the coagulation bath is water or a mixture of water and solvent.
[0088] Step 5: Post-treatment and cross-linking
[0089] After the nascent hollow fiber membrane fibers are completely solidified in a coagulation bath, they are washed with water, subjected to heat treatment for crosslinking, plasticized with glycerol, and dried to obtain a composite hollow fiber dialysis membrane. The heat treatment for crosslinking is carried out at a temperature of 80~150℃ for 2~8 hours. When the heat treatment temperature is below 80℃, the crosslinking reaction is insufficient and the crosslinking density of the interpenetrating network structure is insufficient. When the temperature is above 150℃, the polymer side chains undergo thermal degradation, and the membrane mechanical properties and heparin-like activity deteriorate.
[0090] When the sulfonation degree of SPAES is controlled within the synergistic range of 40%–60%, the sulfonation degree of SPVA is controlled within the 30%–50% range, and the mass ratio of the two is controlled within the 7:3–6:4 range, the anticoagulant performance (PRT) of the composite membrane is improved by 50%–70% compared with that of the pure SPAES membrane. However, if the sulfonation degree of SPAES is higher than 70% or the mass ratio of SPVA is lower than 10%, the improvement effect drops sharply to below 10%. This indicates that there is a non-linear synergistic effect between SPAES and SPVA, rather than a simple performance additive effect. The mechanism may be that within this synergistic range, the flexible / rigid backbone of SPAES and the flexible segments of SPVA form a moderately dense interpenetrating network through chemical cross-linking. This ensures the effective exposure of sulfonic acid groups on the SPVA molecular chain, thereby fully exerting the heparin-like biological activity, while avoiding the destruction of the network structure due to excessive swelling of SPVA. When the sulfonation of SPVA is too high, excessive water absorption by the membrane leads to excessive dilution of the SPVA segments, resulting in a decrease in the effective concentration of sulfonic acid groups. Conversely, when the mass ratio of SPVA is too low, the absolute number of sulfonic acid groups is insufficient to form enough heparin-like active sites. The discovery of this synergistic effect provides strong support for the inventiveness of the technical solution of this invention.
[0091] The hollow fiber dialysis membranes prepared in the embodiments and comparative examples of the present invention were subjected to performance tests according to the following methods:
[0092] (a) Pure water flux test
[0093] Hollow fiber membranes were fabricated into small modules with an effective length of 20 cm (effective membrane area approximately 0.005 m²). The modules were pre-pressed with deionized water at 0.01 MPa for 30 min, and then the pure water flux was measured at 0.1 MPa. The pure water flux was calculated using formula (1):
[0094] J=V / (A×t×P) (1)
[0095] Where J is the pure water flux (L·m–2·h–1·bar–1), V is the permeate water volume (L), A is the effective membrane area (m2), t is the test time (h), and P is the operating pressure (bar). Each sample was tested 3 times, and the average value was taken.
[0096] (ii) Bovine serum albumin (BSA) retention rate test
[0097] Using phosphate-buffered saline (PBS, pH=7.4) containing 1 g / L bovine serum albumin (BSA, Mw=67 kDa) as the feed solution, the permeate was collected after running at 0.1 MPa for 30 min. The absorbance of the feed solution and the permeate was measured at 280 nm using a UV-Vis spectrophotometer. The BSA rejection rate was calculated according to formula (2):
[0098] R=(1–Cp / Cf) × 100% (2)
[0099] Where R is the rejection rate (%), Cp is the BSA concentration in the permeate (g / L), and Cf is the BSA concentration in the feed solution (g / L). Each sample was tested three times, and the average value was taken.
[0100] (III) Lysozyme and β2-microglobulin clearance rate test
[0101] Referring to the standards of "Terminology for Blood Purification" (GB / T 13074) and "Concentrates for Hemodialysis and Related Therapies" (YY 0053-2016), the test was conducted using extracorporeal circulation mode. Simulated plasma containing lysozyme (14 kDa, concentration 50 mg / L) and β2-microglobulin (11.8 kDa, concentration 10 mg / L) was used as the test solution. After running for 4 hours under conditions of 100 mL / min blood flow, 30 mL / min dialysate flow, and 100 mmHg transmembrane pressure, samples were taken for analysis. The concentrations of lysozyme and β2-microglobulin in the feed solution and permeate were determined by high-performance liquid chromatography (HPLC). The clearance rate was calculated according to formula (3):
[0102] Clearance=(Cin–Cout) / Cin×100% (3)
[0103] Wherein, Cin is the initial concentration in the test solution (mg / L), and Cout is the concentration in the permeate (mg / L).
[0104] (iv) Plasma recalcification time (PRT) test
[0105] The method for determining coagulation time was followed according to the national standard "Biological Evaluation of Medical Devices Part 4: Selection of Blood Interaction Tests" (GB / T16886.4). Membrane material was cut into 1 cm × 1 cm sheets and placed in test tubes. 1 mL of anemic platelet-rich plasma (PPP, prepared from fresh sodium citrate-anticoagulated human whole blood by centrifugation at 1500 rpm for 15 min) was added, and the tubes were incubated in a 37°C water bath for 30 min. Then, 0.1 mL of 0.025 M CaCl2 solution was added, and the time (in seconds) required for plasma coagulation from the addition of CaCl2 was immediately recorded. Each sample was tested five times, and the average value was taken. Using pure SPAES membranes as a control, the PRT extension rate was calculated.
[0106] PRT elongation rate = (PRT sample – PRT control) / PRT control × 100% (4)
[0107] (v) Platelet adhesion test
[0108] Following GB / T 16886.4 standard, the membrane material was cut into 1 cm × 1 cm sheets and incubated with platelet-rich plasma (PRP, prepared from fresh sodium citrate-anticoagulated human whole blood by centrifugation at 800 rpm for 10 min) at 37°C for 60 min. After incubation, the membrane was gently washed three times with PBS to remove unadhered platelets. Subsequently, the membrane was fixed with 2.5% glutaraldehyde solution for 30 min, dehydrated with graded ethanol, and the morphology and number of platelets adhering to the membrane surface were observed using scanning electron microscopy (SEM). Ten fields of view (×2000x) were randomly selected from each sample group for counting, the average value was calculated, and the platelet adhesion reduction rate was calculated by comparing it with a pure SPAES membrane control.
[0109] (vi) Flux Recovery Rate (FRR) Test – Evaluation of Pollution Resistance
[0110] Referring to the above pure water flux test method, the initial pure water flux (J0) of the membrane sample was first determined. Then, using a PBS solution of 1 g / L BSA as the contaminant, the membrane was filtered at 0.1 MPa pressure for 60 min, and the pure water flux after contamination (J1) was determined. After backwashing the contaminated membrane sample with PBS for 10 min, the pure water flux (J2) was determined again. The flux recovery rate was calculated according to formula (5):
[0111] FRR=J2 / J0×100% (5)
[0112] Wherein, FRR is the flux recovery rate (%), J0 is the initial pure water flux (L·m–2·h–1·bar–1), and J2 is the pure water flux after cleaning (L·m–2·h–1·bar–1). Each group of samples was tested 3 times, and the average value was taken.
[0113] (vii) 48-hour continuous operation test under simulated CRRT conditions
[0114] An extracorporeal circulation testing platform was constructed, using PBS solution containing BSA (1 g / L) and lysozyme (50 mg / L) as the test solution. The system was continuously operated for 48 h under conditions of blood flow rate of 100 mL / min, dialysate flow rate of 30 mL / min, and transmembrane pressure of 100 mmHg. Samples were taken at 0, 6, 12, 24, 36, and 48 h to determine the lysozyme concentration in the permeate, and the pure water flux was measured at each time point. The flux retention rate was calculated according to formula (6):
[0115] Flux retention rate = Jt / J0 × 100% (6)
[0116] Where Jt is the pure water flux after t hours of operation (L·m–2·h–1·bar–1), and J0 is the initial pure water flux (L·m–2·h–1·bar–1). Each sample group was tested 3 times, and the average value was taken.
[0117] (viii) Mechanical property testing
[0118] Referring to the standard "Determination of Tensile Properties of Plastics Part 1: General" (GB / T 1040.1), the tensile strength and elongation at break of hollow fiber membranes were determined using a universal testing machine. After equilibrating the membrane samples in a standard environment (temperature 23±2℃, relative humidity 50±5%) for 24 h, a monofilament sample with an effective length of 50 mm was taken and tested at a tensile speed of 10 mm / min. The tensile strength was calculated according to formula (7):
[0119] σ=F / S (7)
[0120] Where is the tensile strength (MPa), F is the maximum tensile force at break (N), and S is the cross-sectional area of the membrane sample (mm2). Each group of samples was tested 10 times, and the average value was taken.
[0121] Example 1
[0122] (1) Preparation of short-side-chain sulfonated polyarylene ether sulfone (SPAES-50)
[0123] Synthesis of Intermediate Product 1: 15.2 g (0.06 mol) of 4,4'-difluorodiphenyl sulfone, 13.0 g (0.05 mol) of 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone, and 20.7 g (0.15 mol) of potassium carbonate were added to a 250 mL three-necked flask equipped with nitrogen protection, a Dean-Stark water separator, and a condenser. 200 mL of DMAc and 60 mL of toluene were added, and the mixture was reacted at 140 °C with stirring for 4 h. After removing the toluene, the temperature was raised to 165 °C and reacted for 7 h. After cooling, the reaction mixture was slowly poured into methanol / water (1:1, v / v) to precipitate the product. After filtration, the product was washed three times with methanol and deionized water, and dried under vacuum at 60 °C for 24 h to obtain a polyarylene ether sulfone intermediate containing amino and hydroxyl bifunctional groups (Product 1, yield approximately 92%).
[0124] Synthesis of Intermediate Product 2: Product 1 (5.0 g) was added to a 100 mL three-necked flask equipped with nitrogen and a condenser. 100 mL of DMAc was added to completely dissolve the product, followed by the addition of 1.3 g (1.1 equiv., relative to the molar number of amino groups) of 1,3-propanesulfonic acid lactone. The reaction was carried out at 70 °C for 15 h. After the solution cooled to room temperature, it was poured into isopropanol to precipitate the product. The precipitate was washed repeatedly with deionized water until neutral and dried under vacuum at 60 °C for 24 h to obtain Intermediate Product 2 (yield approximately 88%). In this step, 1,3-propanesulfonic acid lactone undergoes a nucleophilic ring-opening reaction with the primary amino group (–NH2) on the polymer side chain to generate a secondary amine sulfonic acid structure containing a sulfonic acid group (–SO3H).
[0125] Synthesis of intermediate product 3: Hydroquinone (4.4 g, 0.04 mol), sodium hydroxide (2.0 g, 0.05 mol), and 1,6-dibromohexane (4.9 g, 0.02 mol) were dissolved in 100 mL of ethanol and refluxed at 80 °C for 6 h under nitrogen protection. The reaction solution was poured into deionized water, and the pH was adjusted to 7 with 0.1 M sulfuric acid. The precipitated white precipitate was filtered, washed repeatedly with deionized water, and dried under vacuum at 60 °C for 24 h to obtain 1,6-di(4-hydroxyphenoxy)hexane (product 3, yield approximately 85%).
[0126] Synthesis of SPAES-50: Product 2 (5.0 g), Product 3 (1.0 g), and potassium carbonate (0.5 g) were added to a 100 mL three-necked flask equipped with nitrogen and a condenser. 30 mL of DMAc was added and stirred to dissolve the product. The reaction mixture was reacted at 160 °C for 2 h. The reaction solution was slowly poured into deionized water to precipitate the product. After washing repeatedly with deionized water, the product was dried under vacuum at 60 °C for 24 h to obtain short-chain sulfonated polyarylene ether sulfone (SPAES-50). ¹H-NMR analysis (using DMSO-d6 as solvent, with the aromatic proton peak at chemical shift δ 7.0–8.5 ppm as an internal standard) and verified by acid-base titration, yielded an IEC value of approximately 1.8 mmol / g for SPAES-50, indicating that each gram of polymer contains 1.8 mmol of sulfonic acid groups, corresponding to a sulfonation degree of 50% (based on an average of 0.5 sulfonic acid groups per repeating unit).
[0127] (2) Preparation of sulfonated polyvinyl alcohol (SPVA-40)
[0128] Weigh 10.0 g of polyvinyl alcohol (PVA, degree of hydrolysis ≥98%, Mw≈85,000–124,000) and add it to 100 mL of dimethyl sulfoxide (DMSO). Stir at 90 °C for 4 h until completely dissolved to obtain a homogeneous and transparent solution. Then, cool the system to an ice-water bath at 0–5 °C. Dissolve 1.5 mL of chlorosulfonic acid (ClSO3H) in 10 mL of DMSO and slowly add it dropwise to the PVA solution over a period of at least 30 min. After the addition is complete, continue stirring in an ice bath for 30 min, then raise the temperature to 5 °C and react for 6 h.
[0129] After the reaction was complete, the reaction solution was slowly poured into 500 mL of anhydrous ethanol for precipitation. The precipitated polymer was collected by filtration and washed repeatedly with anhydrous ethanol 3-5 times until the washing solution was neutral. The obtained product was dried in a vacuum drying oven at 60 °C for 24 h to obtain sulfonated polyvinyl alcohol (SPVA-40) powder. The IEC value of SPVA-40 was approximately 1.6 mmol / g, and the degree of sulfonation was approximately 40%, as determined by 1H-NMR (using D2O as solvent, with the –CH2–CH(OH)– main chain proton peak at δ 3.6–4.0 ppm as an internal standard) and verified by acid-base titration.
[0130] (3) Preparation of casting solution
[0131] SPAES-50 and SPVA-40 were blended at a mass ratio of 7:3 and dissolved in N-methylpyrrolidone (NMP). The mixture was stirred at 80°C for 8 hours to prepare a solution with a total solid content of 18 wt%. 5 wt% glutaraldehyde (25% aqueous solution) relative to the total polymer mass was added as a crosslinking agent, and 10 wt% polyvinylpyrrolidone (K30) was added as a pore-forming additive. The mixture was stirred for another 3 hours and then allowed to stand for 24 hours to degas.
[0132] (4) Spinning of hollow fiber membranes
[0133] The degassed casting solution was extruded through a hollow fiber spinneret (outer diameter / inner diameter = 0.8 mm / 0.5 mm) at an extrusion speed of 15 m / min for a dry spinning distance of 10 cm before being solidified in a 40°C water coagulation bath. The core solution was a 60 wt% NMP aqueous solution with a flow rate of 5 mL / min.
[0134] (5) Post-processing
[0135] The nascent hollow fiber membrane was thoroughly cleaned in a 40°C water bath for 48 hours to remove residual solvents and pore-forming additives. Then, it was heat-treated at 120°C for 4 hours for crosslinking, followed by plasticizing with a 30 wt% glycerol aqueous solution for 30 minutes, and then vacuum-dried at 60°C for 12 hours to obtain a composite hollow fiber dialysis membrane.
[0136] (6) Performance testing
[0137] The performance indicators were measured according to the above-described "Performance Testing Method". The performance results of the composite hollow fiber dialysis membrane prepared in Example 1 are as follows:
[0138] Pure water flux (according to Method 1): 350 ± 15 L·m–2·h–1·bar–1;
[0139] BSA retention rate (according to Method 2): 92.0 ± 1.5%;
[0140] Lysozyme clearance rate (according to method 3): 58.0 ± 2.0%;
[0141] β2-microglobulin clearance rate (according to method 3): 52.0 ± 2.0%;
[0142] Plasma recalcification time (according to method 4): 363 ± 12 s (65% longer than pure SPAES membrane);
[0143] Platelet adhesion reduction rate (according to method five): ≥60%;
[0144] Flux recovery rate (according to method six): 95.8 ± 1.2%;
[0145] 48-hour flux retention rate (according to Method 7): 85.0 ± 2.0%;
[0146] Tensile strength (according to Method 8): 28.0 ± 1.5 MPa;
[0147] Elongation at break (according to method eight): 12.0 ± 1.0%.
[0148] Example 2
[0149] (1) Preparation of short-side-chain sulfonated polyarylene ether sulfone (SPAES-40)
[0150] Following the method of Example 1, by adjusting the electrophilic sulfonation reaction time (shortened to 4 h), a short-side-chain sulfonated polyarylene sulfone (SPAES-40) with a sulfonation degree of 40% (IEC value of approximately 1.4 mmol / g) was obtained by 1H-NMR and acid-base titration. The remaining operations were the same as in Example 1.
[0151] (2) Preparation of sulfonated polyvinyl alcohol (SPVA-30)
[0152] Following the method of Example 1, the amount of chlorosulfonic acid added was adjusted to 1.0 mL, the reaction time was adjusted to 4 h, and sulfonated polyvinyl alcohol (SPVA-30) with a degree of sulfonation of 30% (IEC value of approximately 1.2 mmol / g) was obtained by 1H-NMR determination. The remaining operations were the same as in Example 1.
[0153] (3) Preparation of casting solution
[0154] SPAES-40 and SPVA-30 were blended at a mass ratio of 8:2 and dissolved in DMAc. The mixture was stirred at 80°C for 8 hours to prepare a solution with a total solids content of 20 wt%. 3 wt% epoxy resin (as a crosslinking agent) and 8 wt% polyethylene glycol (PEG-400) (as a pore-forming additive) were added relative to the total polymer mass. The mixture was stirred for another 3 hours and then allowed to stand for 24 hours to degas.
[0155] (4) Spinning of hollow fiber membranes
[0156] Same as Example 1.
[0157] (5) Post-processing
[0158] Same as Example 1.
[0159] (6) Performance testing
[0160] The performance indicators were measured according to the above-described "Performance Testing Method". The performance results of the composite hollow fiber dialysis membrane prepared in this embodiment are as follows:
[0161] Pure water flux (according to Method 1): 320 ± 12 L·m–2·h–1·bar–1;
[0162] BSA retention rate (according to Method 2): 94.0 ± 1.0%;
[0163] Lysozyme clearance rate (according to method 3): 52.0 ± 2.0%;
[0164] β2-microglobulin clearance rate (according to method 3): 48.0 ± 2.0%;
[0165] Plasma recalcification time (according to method 4): 341 ± 10 s (55% longer than pure SPAES membrane);
[0166] Platelet adhesion reduction rate (according to method five): ≥52%;
[0167] Flux recovery rate (according to Method 6): 93.5 ± 1.5%;
[0168] 48-hour flux retention rate (according to Method 7): 88.0 ± 2.0%;
[0169] Tensile strength (according to Method 8): 32.0 ± 1.5 MPa;
[0170] Elongation at break (according to method eight): 10.0 ± 1.0%.
[0171] Example 3
[0172] (1) Preparation of short-side-chain sulfonated polyarylene ether sulfone (SPAES-60)
[0173] Following the method of Example 1, by adjusting the electrophilic sulfonation reaction time (extending it to 10 h), a short-side-chain sulfonated polyarylene sulfone (SPAES-60) with a sulfonation degree of 60% (IEC value of approximately 2.2 mmol / g) was obtained by 1H-NMR and acid-base titration. The remaining operations were the same as in Example 1.
[0174] (2) Preparation of sulfonated polyvinyl alcohol (SPVA-50)
[0175] Following the method of Example 1, the amount of chlorosulfonic acid added was adjusted to 2.5 mL, the reaction time was adjusted to 10 h, and sulfonated polyvinyl alcohol (SPVA-50) with a degree of sulfonation of 50% (IEC value of approximately 2.0 mmol / g) was obtained by 1H-NMR determination. The remaining operations were the same as in Example 1.
[0176] (3) Preparation of casting solution
[0177] SPAES-60 and SPVA-50 were blended at a mass ratio of 6:4 and dissolved in DMSO. The mixture was stirred at 80°C for 8 hours to prepare a solution with a total solids content of 16 wt%. 6 wt% glutaraldehyde (25% aqueous solution) relative to the total polymer mass was added as a crosslinking agent, and 12 wt% polyvinylpyrrolidone (K30) was added as a pore-forming additive. The mixture was stirred for another 3 hours and then allowed to stand for 24 hours to degas.
[0178] (4) Spinning of hollow fiber membranes
[0179] Same as Example 1.
[0180] (5) Post-processing
[0181] Same as Example 1.
[0182] (6) Performance testing
[0183] The performance indicators were measured according to the above-described "Performance Testing Method". The performance results of the composite hollow fiber dialysis membrane prepared in this embodiment are as follows:
[0184] Pure water flux (according to Method 1): 380 ± 18 L·m–2·h–1·bar–1;
[0185] BSA retention rate (according to Method 2): 90.0 ± 1.5%;
[0186] Lysozyme clearance rate (according to method 3): 62.0 ± 2.0%;
[0187] β2-microglobulin clearance rate (according to method 3): 56.0 ± 2.0%;
[0188] Plasma recalcification time (according to method 4): 374 ± 14 s (70% longer than pure SPAES membrane);
[0189] Platelet adhesion reduction rate (according to method five): ≥65%;
[0190] Flux recovery rate (according to Method 6): 92.0 ± 1.5%;
[0191] 48-hour flux retention (according to Method 7): 82.0 ± 2.5%;
[0192] Tensile strength (according to Method 8): 25.0 ± 1.5 MPa;
[0193] Elongation at break (according to method eight): 14.0 ± 1.5%.
[0194] Comparative Example 1 (Pure SPAES membrane)
[0195] Pure SPAES-50 hollow fiber membranes (without SPVA and without crosslinking agents) were prepared using the same method as in Example 1.
[0196] Performance testing:
[0197] The performance indicators were measured according to the above "performance testing method", and the results are as follows:
[0198] Pure water flux (according to Method 1): 280 ± 10 L·m–2·h–1·bar–1;
[0199] BSA retention rate (according to Method 2): 93.0 ± 1.0%;
[0200] Lysozyme clearance rate (according to method 3): 35.0 ± 2.0%;
[0201] β2-microglobulin clearance rate (according to method 3): 30.0 ± 2.0%;
[0202] Plasma recalcification time (according to method four): 220 ± 8 s;
[0203] Platelet adhesion reduction rate (according to method 5): — (baseline control);
[0204] Flux recovery rate (according to Method 6): 78.0 ± 2.0%;
[0205] 48-hour flux retention rate (according to Method 7): 70.0 ± 3.0%;
[0206] Tensile strength (according to Method 8): 35.0 ± 1.5 MPa;
[0207] Elongation at break (according to method eight): 8.0 ± 1.0%.
[0208] Comparative Example 2 (SPAES / Unsulfonated PVA Composite Membrane)
[0209] The composite hollow fiber membrane was prepared using the same method as in Example 1, but with unsulfonated PVA (degree of alcoholysis ≥98%, Mw≈85,000–124,000) instead of SPVA-40. The mass ratio of SPAES-50 to PVA was 7:3, and 5 wt% glutaraldehyde crosslinking agent was added. The remaining operations were the same as in Example 1.
[0210] Performance testing:
[0211] The performance indicators were measured according to the above "performance testing method", and the results are as follows:
[0212] Pure water flux (according to Method 1): 300 ± 12 L·m–2·h–1·bar–1;
[0213] BSA retention rate (according to Method 2): 92.0 ± 1.5%;
[0214] Lysozyme clearance rate (according to method 3): 42.0 ± 2.0%;
[0215] β2-microglobulin clearance rate (according to method 3): 38.0 ± 2.0%;
[0216] Plasma recalcification time (according to method 4): 253 ± 10 s (approximately 15% longer than that of pure SPAES membrane);
[0217] Platelet adhesion reduction rate (according to method five): approximately 15%;
[0218] Flux recovery rate (according to Method 6): 88.0 ± 2.0%;
[0219] 48-hour flux retention rate (according to Method 7): 78.0 ± 2.5%;
[0220] Tensile strength (according to Method 8): 30.0 ± 1.5 MPa;
[0221] Elongation at break (according to method eight): 11.0 ± 1.0%.
[0222] Comparative Example 3 (High-sulfonation SPAES / high-sulfonation SPVA composite membrane)
[0223] The procedure was the same as in Example 1, but the degree of sulfonation of SPAES was 80% (SPAES-80, IEC value approximately 2.9 mmol / g) and the degree of sulfonation of SPVA was 60% (SPVA-60, IEC value approximately 2.4 mmol / g), with a mass ratio of 7:3. The remaining procedures were the same as in Example 1.
[0224] Performance testing:
[0225] The performance indicators were measured according to the above "performance testing method", and the results are as follows:
[0226] Pure water flux (according to Method 1): 420 ± 20 L·m–2·h–1·bar–1;
[0227] BSA retention rate (according to Method 2): 72.0 ± 2.0%;
[0228] Lysozyme clearance rate (according to method 3): 68.0 ± 2.0%;
[0229] β2-microglobulin clearance rate (according to method 3): 62.0 ± 2.0%;
[0230] Plasma recalcification time (according to method 4): 392 ± 15 s (78% longer than pure SPAES membrane);
[0231] Platelet adhesion reduction rate (according to method five): ≥70%;
[0232] Flux recovery rate (according to Method 6): 72.0 ± 2.5%;
[0233] 48-hour flux retention rate (according to Method 7): 60.0 ± 3.0%;
[0234] Tensile strength (according to Method 8): 18.0 ± 1.5 MPa;
[0235] Elongation at break (according to method eight): 6.0 ± 1.0%;
[0236] Note: In this comparative example, after soaking in PBS for 24 h, the membrane outer diameter expanded from the original 0.80 mm to 0.95 mm (expansion rate of approximately 19%), the membrane wall thickness increased from the original 0.15 mm to 0.18 mm, and the tensile strength decreased to 18 MPa, indicating significant swelling and deformation of the membrane. This demonstrates that while excessive sulfonation can improve anticoagulant performance and middle-molecule clearance rate, it severely impairs dimensional stability and selectivity, failing to meet the clinical requirements for long-term CRRT operation.
[0237] Comparative Example 4 (Physical blending control – non-chemical crosslinking)
[0238] The same method as in Example 1 was followed, but without adding a crosslinking agent to SPAES-50 and SPVA-40, and without heat treatment crosslinking, the composite film was prepared by physical blending only, and the rest of the operation was the same as in Example 1.
[0239] Performance testing:
[0240] The performance indicators were measured according to the above "performance testing method", and the results are as follows:
[0241] Pure water flux (according to Method 1): 340 ± 15 L·m–2·h–1·bar–1;
[0242] BSA retention rate (according to Method 2): 91.0 ± 1.5%;
[0243] Lysozyme clearance rate (according to method 3): 56.0 ± 2.0%;
[0244] β2-microglobulin clearance rate (according to method 3): 50.0 ± 2.0%;
[0245] Plasma recalcification time (according to method 4): 356 ± 12 s (62% longer than pure SPAES membrane);
[0246] Platelet adhesion reduction rate (according to method five): ≥58%;
[0247] Flux recovery rate (according to Method 6): 88.0 ± 2.0%;
[0248] 48-hour flux retention rate (according to Method 7): 68.0 ± 3.0%;
[0249] Tensile strength (according to Method 8): 22.0 ± 1.5 MPa;
[0250] Elongation at break (according to Method 8): 15.0 ± 1.5%;
[0251] Performance degradation after long-term operation: After 24 hours of simulated CRRT operation, SPVA gradually precipitated from the membrane (ATR-FTIR analysis confirmed a decrease of approximately 60% in the intensity of the characteristic peak of the sulfonic acid group), the PRT elongation decreased from the initial 62% to 18%, the 48-hour flux retention decreased to 68%, and the tensile strength decreased to 18 MPa. This comparative example demonstrates that chemical crosslinking is a necessary condition for achieving stable anchorage of SPVA in the membrane network and ensuring long-acting heparin-like activity.
[0252]
[0253] Table 1 shows the preparation conditions and performance of each example and comparative example.
[0254] As shown in Table 1, this invention, through the synergistic compounding of SPAES and SPVA, significantly improves the anticoagulant, middle-molecule clearance, and antifouling properties of the membrane while maintaining excellent mechanical properties. Comparative Example 1 (pure SPAES) exhibits the best mechanical properties, but its anticoagulant and middle-molecule clearance capabilities are significantly insufficient. Comparative Example 2 (unsulfonated PVA compound) shows no significant improvement in anticoagulant properties, demonstrating that the sulfonic acid groups of SPVA are key to achieving heparin-like activity. Comparative Example 3 (over-sulfonated) further improves anticoagulant and middle-molecule clearance properties, but its selectivity and dimensional stability are severely degraded, failing to meet the clinical requirements of CRRT. Comparative Example 4 (no chemical crosslinking) initially shows performance close to that of Example 1, but its performance rapidly declines after long-term operation due to SPVA loss, proving that chemical crosslinking is a necessary condition for achieving long-term stability.
[0255] like Figure 1-3 As shown, the inner surface separation layer of the hollow fiber membrane of the present invention is dense and defect-free, corresponding to the separation functional layer; the interior of the membrane wall has an asymmetric structure composed of finger-like pores and sponge-like pores, corresponding to the support layer. The dense structure of the separation layer originates from the kinetic regulation of the SPAES / SPVA interpenetrating network (formed through intermolecular crosslinking) during the phase separation process.
Claims
1. A heparin-like interpenetrating network CRRT hollow fiber dialysis membrane, comprising short-side-chain sulfonated polyarylene ether sulfone and sulfonated polyvinyl alcohol, characterized in that, The short-side-chain sulfonated polyarylene ether sulfone and sulfonated polyvinyl alcohol form an interpenetrating network structure through chemical crosslinking or physical crosslinking. The chemical crosslinking is achieved by forming covalent crosslinking points through esterification reaction between the sulfonic acid groups on the short-side-chain sulfonated polyarylene ether sulfone segments and the hydroxyl groups on the sulfonated polyvinyl alcohol segments. The physical crosslinking is achieved through at least one of the following: hydrogen bonding between the sulfonic acid groups on the short-side-chain sulfonated polyarylene ether sulfone segments and the hydroxyl groups on the sulfonated polyvinyl alcohol segments; ionic crosslinking between the sulfonic acid groups and multivalent metal ions; or hydrophobic interactions between polymer segments.
2. The heparin-like interpenetrating network CRRT hollow fiber dialysis membrane as described in claim 1, characterized in that, The sulfonic acid groups of the short-side-chain sulfonated polyarylene sulfone are connected to the polyarylene sulfone main chain by a linking chain of no more than 3 atoms, and the side chain length is less than or equal to 6 atoms.
3. The heparin-like interpenetrating network CRRT hollow fiber dialysis membrane as described in claim 2, characterized in that, The connecting chain is –C3H6– or –C6H4–.
4. The heparin-like interpenetrating network CRRT hollow fiber dialysis membrane as described in claim 1, characterized in that, The degree of sulfonation of the short-side-chain sulfonated polyarylene sulfone is 30% to 70%, preferably 40% to 60%; the degree of sulfonation of the sulfonated polyvinyl alcohol is 20% to 60%, preferably 30% to 50%.
5. The heparin-like interpenetrating network CRRT hollow fiber dialysis membrane as described in claim 1, characterized in that, The mass ratio of the short-side-chain sulfonated polyarylether sulfone to sulfonated polyvinyl alcohol is 9:1 to 5:5, preferably 7:3 to 6:
4.
6. The heparin-like interpenetrating network CRRT hollow fiber dialysis membrane as described in claim 1, characterized in that, The hollow fiber membrane has an asymmetrical structure, with a dense separation layer on the inner surface and a sponge-like support structure on the outer surface and inside the membrane wall.
7. A method for preparing a heparin-like interpenetrating network (IPN) hollow fiber dialysis membrane for CRRT as described in any one of claims 1-6, characterized in that... Includes the following steps: (1) Dissolve short-side-chain sulfonated polyarylether sulfone and sulfonated polyvinyl alcohol in a common solvent at a mass ratio of 9:1 to 5:5, and stir at 60 to 100°C for 4 to 12 hours to form a homogeneous casting solution. (2) Add crosslinking agent and pore-forming additive to the casting solution, continue stirring for 2-4 hours, and let stand to degas for 12-24 hours; the crosslinking agent is selected from at least one of glutaraldehyde, epoxy resin or thermal crosslinking agent; the pore-forming additive is selected from at least one of polyvinylpyrrolidone and polyethylene glycol; (3) The degassed casting liquid is extruded through the hollow fiber spinning spinneret and solidified in the coagulation bath through a dry-wet spinning process to form the hollow fiber membrane filament. (4) After the hollow fiber membrane nascent fibers are completely solidified in a coagulation bath, they are washed with water, subjected to heat treatment for crosslinking, plasticized with glycerol, and dried to obtain the hollow fiber dialysis membrane.
8. The preparation method according to claim 7, characterized in that: The common solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, and N,N-dimethylformamide.
9. The preparation method according to claim 7, characterized in that: The process parameters for the dry-wet spinning process in step (3) are: extrusion speed 5~30 m / min, dry spinning length 5~50 cm, coagulation bath temperature 20~60℃; the temperature for heat treatment crosslinking in step (4) is 80~150℃, and the time is 2~8 hours.
10. The use of the heparin-like interpenetrating network CRRT hollow fiber dialysis membrane as described in any one of claims 1-6 in the preparation of a blood purification filter for continuous renal replacement therapy.
Citation Information
Patent Citations
Gas solution supply device and method performed using same
CN117643807A
Hemodialysis membrane with self-anticoagulation function and preparation method thereof
CN119857370A
A method of operating an alignment station for slices, and an alignment station for performing said method
WO2020130823A1